Prática de ensino supervisionada em educação pré-escolar e do ensino do 1º ciclo do ensino básico - Ortega, Maria Isabel Teixeira de Azevedo (2010)
Prática de ensino supervisionada em educação pré-escolar e do ensino do 1º ciclo do ensino básico. Of this work emerges the professional practice developed in a context of rural environment with students from 1st and 2nd year, and was designed to acquire data which would allow me to guide the socio-emotional development of students specifically on identifying emotions. The purpose is to know if the narrative that I tell the students can be an effective learning strategy and rich in learning. To prove the hypothesis, the emotional development of pupils can be achieved through the identification of emotional states present in some narratives in the pedagogic:al practice, a methodology of qualitative slant was used which entered in the interpretative paradigm. The sample was comprised of 10 students aged between five and seven years old. The construct theory is corroborated by the responses of the sample in relation to the identification of emotional states present in the narrative. In conclusion this work contributes to give consistency to the idea expressed throughout the work, that there are cultural factors that can be taught and learned, that lead to emotional and social development, through emotions in educational contexts of intentionality.